The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2024
DOI: 10.1039/d3cp05061k
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependence of X-ray stability and degradation mechanisms at lead halide perovskite single crystal surfaces

Alberto García-Fernández,
Birgit Kammlander,
Stefania Riva
et al.

Abstract: We studied the X-ray stability of five different clean perovskite single crystal surfaces (MAPbI3, MAPbBr3, MAPbCl3, FAPbBr3, CsPbBr3) via photoelectron spectroscopy and observed different degradation paths depending on the exact composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Gao et al conducted research on the effect of X-ray radiation on a single crystal of MAPbBr 3 in a vacuum environment, revealing that approximately 10% of the surface MAPbBr 3 was degraded into metallic lead (Figure 3d) [39]. Furthermore, recent work by Cappel et al delved deeper into the effects of X-ray radiation on single crystals comprising different components under vacuum conditions [40]. Those findings indicated that only a small amount of metallic lead was formed in MAPbI 3 and CsPbBr 3 single crystals.…”
Section: X-raymentioning
confidence: 99%
“…Gao et al conducted research on the effect of X-ray radiation on a single crystal of MAPbBr 3 in a vacuum environment, revealing that approximately 10% of the surface MAPbBr 3 was degraded into metallic lead (Figure 3d) [39]. Furthermore, recent work by Cappel et al delved deeper into the effects of X-ray radiation on single crystals comprising different components under vacuum conditions [40]. Those findings indicated that only a small amount of metallic lead was formed in MAPbI 3 and CsPbBr 3 single crystals.…”
Section: X-raymentioning
confidence: 99%
“…In the lower equatorial orbit LEO, total ionizing dose (TID) is estimated to be around 3–10 krad per year. 11 To imitate space radiation on the Earth, various facilities with different particles and energies are used: protons, 12,13 electrons, 2,14 X-rays 10,15,16 and gamma-rays. 5,7–9,17–22 Normally, electron irradiation is used due to the vast availability of electron beam setups.…”
Section: Introductionmentioning
confidence: 99%